Decision Support System for Determining Mini Sugar Mill Location in Madura - Mokh. Rum; Dwidjono Hadi Darwanto; Slamet Hartono; Masyhuri Masyhuri (Universitas Sebelas Maret, 2019)
Madura has widely potential farming business of sugarcane and has enough raw material to build a mini sugar mill. Sugarcane is cultivated in Madura, particularly in four regencies, namely Bangkalan, Sampang, Pamekasan and Sumenep. To decide the location of mini sugar mill in one of the regencies requires decision support system (DSS). This study aimed to determine the priority of mini sugar mill location in Madura. This research used primary and secondary data. The primary data were collected using questionnaires. Then, the results of evaluation from the experts, on the items of questions, were analyzed with analytical hierarchy process (AHP). This was accomplished using Expert Choice 2000 software. Analysis of the selection of mini sugar mill location considered six criteria, namely the land suitability level, existing infrastructure, the potential of raw materials, the availability of labor, social capital and institutions. The selected criteria were further classified into sub-criteria to clarify the definitions of operational criteria and facilitate assessment for respondents. The results show that social capital had the greatest influence on decision making, followed by the land suitability level and the potential of raw materials. The finding in this research is that the mini sugar mill location is given priority in Bangkalan Regency, Madura. The conclusion of this research is that AHP analysis can be used as a method to take accurate decision in determining the location of sugarcane factory in certain area of sugarcane farming business development.